Junin Virus Activates p38 MAPK and HSP27 Upon Entry - Fitzpatrick, Collin J.; Mudhasani, Rajini R.; Altamura, Louis A.; Campbell, Catherine E.; Tran, Julie P.; Beitzel, Brett F.; Narayanan, Aarthi; de la Fuente, Cynthia L.; Kehn-Hall, Kylene; Smith, Jeffrey M.; Schmaljohn, Connie S.; Garrison, Aura R. (Frontiers in Cellular and Infection Microbiology, 2022)
Junín virus (JUNV), a New World arenavirus, is a rodent-borne virus and the causative agent of Argentine hemorrhagic fever. Humans become infected through exposure to rodent host secreta and excreta and the resulting infection can lead to an acute inflammatory disease with significant morbidity and mortality. Little is understood about the molecular pathogenesis of arenavirus hemorrhagic fever infections. We utilized Reverse Phase Protein Microarrays (RPPA) to compare global alterations in the host proteome following infection with an attenuated vaccine strain, Candid#1 (CD1), and the most parental virulent strain, XJ13, of JUNV in a human cell culture line. Human small airway epithelial cells were infected with CD1 or XJ13 at an MOI of 10, or mock infected. To determine proteomic changes at early timepoints (T = 1, 3, 8 and 24 h), the JUNV infected or mock infected cells were lysed in compatible buffers for RPPA. Out of 113 proteins that were examined by RPPA, 14 proteins were significantly altered following JUNV infection. Several proteins were commonly phosphorylated between the two strains and these correspond to entry and early replication events, to include p38 mitogen-activated protein kinase (MAPK), heat shock protein 27 (HSP27), and nuclear factor kappa B (NFκB). We qualitatively confirmed the alterations of these three proteins following infection by western blot analysis. We also determined that the inhibition of either p38 MAPK, with the small molecule inhibitor SB 203580 or siRNA knockdown, or HSP27, by siRNA knockdown, significantly decreases JUNV replication. Our data suggests that HSP27 phosphorylation at S82 upon virus infection is dependent on p38 MAPK activity. This work sheds light on the nuances of arenavirus replication.